Early and late Biliary Complications of Laparoscopic Cholecystectomy in Acute Cholecystitis - Khattab, Omar Salem (AL-Kindy College Medical Journal, 2011)
Background: Laparoscopic cholecystectomy has become the standard of care for the elective management of cholelithiasis. Little information exists, however, regarding the appropriateness of this procedure in the setting of acute symptomatology. Objective: This study was designed to evaluate the outcome of laparoscopic cholecystectomy in acute and severe acute cholecystitis based on early and late biliary complications, their incidence and management, and conversion rates to open surgery. Methods: A prospective study done between April 2007 and November 2010, in the department of general surgery, medical city teaching hospital, Baghdad. Includes patients with acute cholecystitis admitted for laparoscopic cholecystectomy; they were divided into two groups, (group 1) including patients with acute cholecystitis; (group 2) including patients with severe acute cholecystitis. Results: 306 patients were admitted for laparoscopic cholecystectomy, 71 (23.2%) of them with acute cholecystitis and was involved in this study; they were divided into two groups, (group 1) patients with acute cholecystitis 61(85.9%), (group 2) patients with severe acute cholecystitis 10 (14%); including gangrenous gallbladder 3(30%), and empyematous gallbladder 7(70%). Patients in group 2 were significantly older than in group 1. Female sex was more significant in group 1, while male sex was more significant in group. There was no procedure related mortality. Conclusion: laparoscopic cholecystectomy for acute cholecystitis is safe and associated with a low morbidity, mortality, and a low conversion rate.